2017
DOI: 10.1111/pin.12513
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological importance of anterior prostate cancer in Japanese Men

Abstract: Prostate cancer of transition zone origin or anterior location has been recognized as infrequent, smaller in size and indolent, whereas, our previous report showed that transition zone/anterior cancer was frequently experienced in Japanese men. The current study was conducted to show clinicopathological characteristics of transition zone/anterior cancer. A total of 201 radical prostatectomy specimens were categorized as cancer of anterior or posterior prostate where more than two thirds of the tumor existed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Several studies from Western countries have shown that the majority of PCa arose in the PZ, and cancer in the TZ was less frequent (4%‐20%) 5–8 . However, our previous study showed that the prevalence of TZ cancer was as much as 42% in a Japanese cohort, and subsequent studies from eastern Asian countries also showed a higher prevalence of TZ cancers (30%‐46%) than those from Western countries 9–13 …”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Several studies from Western countries have shown that the majority of PCa arose in the PZ, and cancer in the TZ was less frequent (4%‐20%) 5–8 . However, our previous study showed that the prevalence of TZ cancer was as much as 42% in a Japanese cohort, and subsequent studies from eastern Asian countries also showed a higher prevalence of TZ cancers (30%‐46%) than those from Western countries 9–13 …”
Section: Introductionmentioning
confidence: 80%
“…[5][6][7][8] However, our previous study showed that the prevalence of TZ cancer was as much as 42% in a Japanese cohort, and subsequent studies from eastern Asian countries also showed a higher prevalence of TZ cancers (30%-46%) than those from Western countries. [9][10][11][12][13] Although the genetic features of PCa remain unclear to date, the racial differences associated with the most frequent genetic alterations of the transmembrane protease, serine 2 (TMPRSS2)v-ets avian erythroblastosis virus E26 oncogene homolog (ERG) gene fusion and phosphatase and tensin homolog (PTEN) inactivation have been reported. The prevalence of the TMPRSS2-ERG gene fusion/ERG-overexpression in PCa was approximately 50% in Western countries, [14][15][16] although the prevalence is less at 10%-20% in east-Asian countries.…”
mentioning
confidence: 99%
“…It has been reported that transitional zone/anterior cancers diagnosed by RP specimens are commonly seen in Japanese cohorts; however, anterior cancers are less aggressive. 16 Additionally, the mpMRI has improved the chances of detecting local invasion whose prognosis are better. Previous studies reported that the maximum joint sensitivity and speci city for detecting local invasion using mpMRI reached 71%.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in diagnostic accuracy, however, remain unclear. Emerging evidence suggests that TP biopsy identifies cancers in the anterior prostate at higher rates than was previously expected, potentially due to the different biopsy trajectory in a TP compared to transrectal approach [8][9][10].…”
Section: Introductionmentioning
confidence: 90%